Analysis of Stock Market Efficiency - Mishra, Basnta Kumar (Economic Journal of Nepal, 2015)
This paper examines the weak form of market efficiency of the Nepalese stock market employing autocorrelation test, runs test, variance ratio test, and unit root test on monthly closing prices and market index for the period mid-2003 to mid-2012. The study result reveals that the monthly return series of Nepalese companies listed in Nepal stock exchange, and market return series do not follow any predictable pattern. It suggests that any speculation based on information on past stock price is fruitless. It implies that all information conveyed in stock price in the past are impounded into the current price of the stock. Thus, the opportunity of making abnormal returns based on information on past stock price in the Nepalese stock market is ruled out. The Economic Journal of Nepal, Vol. 35, No. 3, July-September 2012 (Issue N0. 139)